2012
DOI: 10.1016/j.cell.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Efficient Correction of ΔF508 CFTR Revealed by Analyses of Evolved Sequences

Abstract: SUMMARY Misfolding of ΔF508 CFTR underlies pathology in most CF patients. F508 resides in the first nucleotide binding domain (NBD1) of CFTR near a predicted interface with the fourth intracellular loop (ICL4). Efforts to identify small molecules that restore function by correcting the folding defect have revealed an apparent efficacy ceiling. To understand the mechanistic basis of this obstacle, positions statistically coupled to 508, in evolved sequences, were identified and assessed for their impact on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
320
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(355 citation statements)
references
References 71 publications
31
320
0
4
Order By: Relevance
“…One possibility is that each corrector interacts with a different structural feature of F508del-CFTR to stabilize their folding or reduce nonproductive folding intermediates. Because the folding defect of F508del involves multiple domain and interdomain interactions, multiple interaction sites may be necessary for optimal correction of the misfolded protein (33)(34)(35)(36)(37). Alternatively, rescue might be achieved indirectly through the modulation of folding chaperones or by suppressing ER-associated degradation (ERAD) quality control pathways that promote F508del-CFTR ubiquitylation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that each corrector interacts with a different structural feature of F508del-CFTR to stabilize their folding or reduce nonproductive folding intermediates. Because the folding defect of F508del involves multiple domain and interdomain interactions, multiple interaction sites may be necessary for optimal correction of the misfolded protein (33)(34)(35)(36)(37). Alternatively, rescue might be achieved indirectly through the modulation of folding chaperones or by suppressing ER-associated degradation (ERAD) quality control pathways that promote F508del-CFTR ubiquitylation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations encompassing the K710 and K716 residues are found in the Toronto CFTR mutation database. Recent research revealed that the ICL4 in CFTR interfaces with the NBD1 domain and that the F508del CFTR mutation interrupts ICL4 and NBD1 domain interactions by altering NBD1 domain folding (30,31). The NBD2 domain is important in ATP binding and hydrolysis for gating (32).…”
Section: Figmentioning
confidence: 99%
“…However, the local structural perturbations caused by the F508del mutation in the folded conformation of NBD1 are likely to contribute at least indirectly to pathogenesis by disrupting structural interactions between NBD1 and the TMDs of CFTR (Lewis et al 2005Serohijos et al 2008;He et al 2010;Loo et al 2010;Thibodeau et al 2010). Recently published work suggests that developing effective drugs to correct the molecular defects caused by the F508del mutation in CFTR may require correction of these disrupted interdomain interactions (Mendoza et al 2012;Rabeh et al 2012).…”
Section: Cftr (Abcc7) Structurementioning
confidence: 99%
“…Although the inability to date to purify the TMDs of CFTR in a native conformational state has prevented direct biophysical evaluation of this hypothesis, its validity is supported by the results from mutagenesis experiments conducted by several different laboratories Loo et al 2010;Thibodeau et al 2010;Mendoza et al 2012;Rabeh et al 2012). These experiments provide evidence that the defective trafficking of F508del-CFTR in tissue culture cells can be suppressed by strengthening the interaction between the perturbed surface on NBD1 and the cognate region of the TMD.…”
Section: Cftr (Abcc7) Structurementioning
confidence: 99%
See 1 more Smart Citation